2003
DOI: 10.17660/actahortic.2003.598.31
|View full text |Cite
|
Sign up to set email alerts
|

Germination Trials and Domestication Potential of Three Native Species With Edible Sprouts: Ruscus Aculeatus L., Tamus Communis L. And Smilax Aspera L.

Abstract: Ruscus aculeatus, Tamus communis and Smilax aspera are wild species whose young spring sprouts are consumed in some areas of Italy. Although sometimes abundant in the natural vegetation, these species are not common on a country basis. Sprouts are therefore only locally commercially available. Cultivation could contribute to make them better known and increase vegetable product differentiation. Seed germination was investigated by applying the following treatments: control, concentrated H 2 SO 4 for 5 or 10 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…We conducted preliminary tests to break the dormancy of seeds of Smilax polyantha collected in 2004, as described by several authors (Andreata 1980, Pogge & Bearce 1989, D'Antuono & Lovato 2003, Santos et al 2003, Shao et al 2006. We used chemical scarification (sulfuric acid) and mechanical (sandpaper), heat shock and gibberillic acid (GA 3 ), following the methodology described by Santos et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted preliminary tests to break the dormancy of seeds of Smilax polyantha collected in 2004, as described by several authors (Andreata 1980, Pogge & Bearce 1989, D'Antuono & Lovato 2003, Santos et al 2003, Shao et al 2006. We used chemical scarification (sulfuric acid) and mechanical (sandpaper), heat shock and gibberillic acid (GA 3 ), following the methodology described by Santos et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors carried out studies about germination of Smilax species (Holm 1890, Andreata 1980, Pogge & Bearce 1989, Andreata & Pereira 1990, Barnea et al 1991, Andreata & Menezes 1999, Rosa & Ferreira 1999, D'Antuono & Lovato 2003, Santos et al 2003, Palhares et al 2009, Martins et al 2011. These studies tested different treatments and they found different results in relation to responses to light, dormancy break and germination rates.…”
mentioning
confidence: 99%
“…The shoots live for several years but do not grow after the first year. New shoots are produced annually from the underground rhizome (D'Antuono & Lovato ; Balica, Tămaş & Deliu ). The wood is typical of monocotyledons with the vascular bundles scattered through the sclerenchyma cylinder (Schweingruber ).…”
Section: Structure and Physiologymentioning
confidence: 99%
“…Ruscus aculeatus has geophyte properties in that it readily produces new shoots from the creeping rhizome, and this appears to be the main method of spread within a locality. D'Antuono and Lovato () in Italy found that seedlings planted out (after germination in climatically controlled chambers) had already produced several new shoots from the roots when 1 year old.…”
Section: Structure and Physiologymentioning
confidence: 99%
See 1 more Smart Citation